Biomass fuel usage for cooking and frailty among older adults in China: a population-based cohort study - Song, Quhong; Dai, Miao; Lin, Taiping; Zhao, Yanli; Peng, Xuchao; Liang, Rui; Su, Qiaoli; Yue, Jirong (Frontiers in Public Health, 2023)
Background Although outdoor air pollution is reported to have a negative effect on frailty, evidence involving household air pollution is sparse. Methods A cohort study on older participants aged ≥65 years from the Chinese Longitudinal Healthy Longevity Survey was conducted between 2011/2012 and 2014. Household cooking fuel types were determined by self-reported questionaries, and were dichotomized into clean or biomass fuels. The frailty status was evaluated via a 46-item frailty index (FI) and the FRAIL scale, respectively. Frailty was identified if FI >0.21 or FRAIL score ≥3. Cox proportional hazards models were employed to examine the relationship between cooking fuels and incident frailty. And the effects of swapping cooking fuels on frailty risk were also explored. Results Among 4,643 participants (mean age at baseline 80.9 ± 9.6 years, 53.7% male) totaling 11,340 person-years, 923 (19.9%) incident frailty was identified using FI. Compared to clean fuels, cooking with biomass fuels was intricately linked to a 23% rise in frailty risk (hazard ratio [HR] 1.23, 95% confidence interval [CI] 1.06–1.43). A similar association was detected between biomass cooking fuels and frailty measured by the FRAIL scale (HR 1.24, 95% CI 1.04–1.50). Sensitive analyses supported the independent relationship between biomass fuels and frailty. Stratified analyses revealed that the frailty risk was higher among town residents (HR 1.44, 95% CI 1.13–1.84) and participants not exercising regularly (HR 1.35, 95% CI 1.11–1.64). In comparison with persistent biomass fuels usage, switching to clean fuels had a trend to reduce the frailty risk, and the opposite effect was observed when swapping from clean to biomass fuels. Conclusion Cooking with biomass fuels was associated with an increased frailty risk in older adults, especially amongst those living in town and those lacking regular exercise. More studies are needed to confirm our findings and to evaluate the potential benefits of reducing indoor biomass fuel usage.